2016
DOI: 10.5409/wjcp.v5.i4.383
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation as an adjunct to standard therapy in childhood nephrotic syndrome - a systematic review

Abstract: AIMTo evaluate the role of zinc as add on treatment to the “recommended treatment” of nephrotic syndrome (NS) in children.METHODSAll the published literature through the major databases including Medline/Pubmed, Embase, and Google Scholar were searched till 31st December 2015. Reference lists from the articles were reviewed to identify additional pertinent articles. Retrieved papers concerning the role of zinc in childhood NS were reviewed by the authors, and the data were extracted using a standardized data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
1
13
1
2
Order By: Relevance
“…The balance of Th-1-Th-2 cytokines may prevent the occurrence of relapse in NS. 15 Homocysteine did not linearly correlate with zinc in our study. After controlling for age and albumin level, homocysteine was observed to have a significant association with zinc by a cubic model.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The balance of Th-1-Th-2 cytokines may prevent the occurrence of relapse in NS. 15 Homocysteine did not linearly correlate with zinc in our study. After controlling for age and albumin level, homocysteine was observed to have a significant association with zinc by a cubic model.…”
Section: Discussioncontrasting
confidence: 73%
“…No zinc deficiency was observed in the first attack NS patients. Previous studies by Arun et al and Bhatt et al showed that zinc supplementation may decrease the incidence of relapse in NS patients, 15,16 due to the effect of zinc in reducing the risk of infection, particularly infection of the gastrointestinal and respiratory tracts.1 6 Zinc deficiency causes downregulation of Th1 cytokines, relative Th-2 bias, and increased risk of infection. Zinc supplementation strengthens IL-1 and interferon gene expression, thereby restoring the Th1 immune response.…”
Section: Discussionmentioning
confidence: 98%
“…They established that addition of zinc to standard treatment of nephrotic syndrome is effective in decreasing of infections and recurrences. (15) Our study also showed that recurrences in nephrotic patients have a relationship between low plasma zinc levels.…”
Section: Discussionsupporting
confidence: 64%
“…A recent meta‐analysis and systematic review of 6 studies evaluated the use of zinc in pediatric patients with SDNS or Frequently Relapsing Nephrotic Syndrome (FRNS) and suggests that zinc therapy added to standard therapy may reduce the number of relapses at 6 months and 12 months and may help induce remission 51 . Although the studies included were found to be of "very low quality," this presents an exciting area for future research on the effects of this micronutrient in pediatric NS 51 . Finally, urinary losses of vitamin B 12 and transcobalamin in pediatric NS have been described, but the impact of this on the development of anemia is unknown 47 …”
Section: Nutrition and Metabolic Complications In Pediatric Nsmentioning
confidence: 99%